Analysing the feasibility of powering the Americas with renewable energy and inter-regional grid interconnections by 2030. (May 2019) - Aghahosseini, Arman; Bogdanov, Dmitrii; Barbosa, Larissa S.N.S.; Breyer, Christian
Abstract: The Sustainable Development Goals and the Paris Agreement, as the two biggest climate action initiatives, address the need to shift towards a fully sustainable energy system. The deployment of renewable energy, especially solar and wind power, decreases carbon dioxide emissions, but presents issues of resource intermittency. In this study, a cost-optimised 100% renewable energy based system is analysed and quantified for the Americas for the reference year 2030 using high spatially and temporally resolved weather data. Several scenarios have been applied, from a decentralised power system towards a fully centralised and interconnected system, taking into account a mix of renewable energy, energy storage and transmission networks. This research aims to evaluate the benefits of an interconnected energy system for the Americas. The levelised cost of electricity (LCOE) is between 48.8 and 59.0 €/MWh depending on the chosen scenario. The results show that the LCOE and total annualised cost drop by 14% and 15%, respectively, in a centralised power system. The optimised utilisation of transmission grids leads to less energy storage requirement. Sector coupling brings further benefits by reducing additional 4% of LCOE, where electricity demand for power, seawater desalination and non-energetic industrial gas sectors have been supplied. A comparison between the interconnected Americas and North and South America individually shows a reduction of 1.6% and 4.0% for the total annual system cost and LCOE. Although the cost of the energy system decreased due to wide grid interconnection, substantial benefits have not been achieved as reported earlier for a Pan-American energy system. A scenario with synthetic natural gas (SNG) trading through a liquefied natural gas value chain has also been presented. The results suggest that local SNG production cost in the assumed consumption centre is almost the same as the cost of imported SNG. Highlights: A 100% renewable energy based system is analysed for the Americas for the year 2030. Interconnected Americas show slightly more benefit than North and South America. Long distance transmission lines cannot compete with energy storage technologies. Renewable energy variability can be resolved at a cost-effective manner. 100% renewable energy systems are lower in cost than a business-as-usual scenario.